Effects of Fossil Fuel Usage in Electricity Production on CO2 Emissions: A STIRPAT Model Application on 20 Selected Countries - Ekrem Yilmaz; Fatma Sensoy (International Journal of Energy Economics and Policy, 2022)
This article examines the causes of air pollution while paying particular attention to the effects of fossil fuel use in electricity generation. Dietz and Roza's (1994) STIRPAT model, which is a reformulated version of the IPAT model, was used. The data includes the 20 countries with the highest CO2 emission levels and covers the years 1991 to 2015. According to the empirical results of this article, increases in population and GDP per capita are followed by a proportional increase in CO2 emissions. Moreover, the results show that the share of coal in electricity generation has a negative impact on CO2 emissions in selected countries. On the other hand, the results show that the share of gas in electricity generation does not have a significant impact on CO2 emissions in selected countries and selected period.